Interpretation of 9 Selected Visual Works of Contemporary Young Talent from the Context of the National Cultural Policy Core - Omran Zailuddin, Firdaus Naif; Abdullah, Muhammad; Berahim, Hawari; Mappon, Azharudin (Idealogy Journal; Vol 3 No 2 (2018): Idealogy Journal (September 2018), 2018)
Contemporary Young Talent (CYT) is a visual arts competition organized by the National Visual Arts Gallery (NVAG) which is the most prestigious in Malaysia. Its 40 years of organization have successfully produced many renowned artists who are now pioneers in the Malaysian and regional visual arts arena. In line with the strength of CYT as a reflection of the future of Malaysian visual arts and the role of art as a cultural vehicle, the objective of the study is to analyze and further dismantle the latest visual art works of Malaysian artists from the perspective of national culture through the CYT platform from 2000 to 2013. This study aims to clearly understand the visual elements and features that are the cultural identity in the latest Malaysian visual arts. This objective was achieved through observation and reading of CYT catalog books published by NVAG, scholarly books, journals, and relevant previous studies as well as interviews on three artists and academics who won the CYT competition. This study uses a qualitative approach, guided by the 4 components of the theory of art criticism Feldman E.B. (1994) namely description, analysis, interpretation and evaluation. 9 works will be analyzed from the aspects of ‘form’ and ‘meaning’. The results of the work analysis will be compared with national cultural elements (data triangulation) and then justify and classify CYT visual art works based on the 3 cores of the National Cultural Policy, namely, the culture of the region's indigenous peoples, other appropriate cultures and Islamic culture through descriptive text.). This study is important to create awareness, deeper appreciation and provide knowledge to art admirers in understanding the meaning and approach and content in the latest visual artwork. The results of the study through descriptive texts explain the existence of national cultural elements and their relationship in selected contemporary works of CYT (2000-2013). Keywords: Interpretation, Contemporary Young Talent, National Cultural Policy